2017
DOI: 10.1111/pace.13141
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐low radiation dose during electrophysiology procedures using optimized new generation fluoroscopy technology

Abstract: An optimized contemporary digital fluoroscopy system, with low radiation dose configuration and continued good procedural practice, can result in ultra-low radiation levels for all electrophysiology procedures, without compromising procedural time or procedural success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…On the other hand, our favorable results in reducing median DAP using customized parameters are encouraging, as also shown by the latest published studies assessing the effect of new technologies dedicated to dose reduction …”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…On the other hand, our favorable results in reducing median DAP using customized parameters are encouraging, as also shown by the latest published studies assessing the effect of new technologies dedicated to dose reduction …”
Section: Discussionsupporting
confidence: 60%
“…Nonfluoroscopic mapping systems with electromagnetic guidance or new shielding equipment result in dose reduction, but they are not commonly used. Improvements in X‐ray generator software, the use of low frame rate fluoroscopy, new generators, and recent technological advances in coronary sinus leads have been shown to reduce radiation exposure, particularly in young patients . The objectives of this study were to describe current radiation protection practices during the implantation of cardiac devices, define dose reference levels, and assess radiation exposure based on the devices currently in use.…”
Section: Introductionmentioning
confidence: 99%
“…There is far less radiation incurred for pacemaker implantation or revision, EP study, or standard radiofrequency ablation, although variances are wide between reported doses. 22…”
Section: Specific Task-based Alternativesmentioning
confidence: 99%
“…Lowering fluoroscopy pulse rates are also a particularly important dose reduction tool during electrophysiology procedures as electrophysiology procedures perform few digital acquisitions so the majority of the radiation exposure comes from fluoroscopy. In a previous study, a modern X‐ray system, with low fluoroscopy pulse rates and a low dose per pulse was demonstrated to reduce DAP by over 90%, when compared to an older generation system . That study also tailored the image processing to this low pulse rate and low dose rate protocol.…”
Section: Electrophysiology Proceduresmentioning
confidence: 99%